2015
DOI: 10.1097/bot.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

Can the Use of Variable-Angle Volar Locking Plates Compensate for Suboptimal Plate Positioning in Unstable Distal Radius Fractures? A Biomechanical Study

Abstract: In this experimental model, variable-angle screws provided a leeway of 3 mm in both the sagittal and coronal directions without sacrificing construct strength, which may considerably facilitate fixation of these difficult fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Previous setups vary in almost every aspect, i.e. boundary conditions, the fracture model, and the specimens used [ 17 20 ]. All of these have a pronounced impact on the biomechanical outcome parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous setups vary in almost every aspect, i.e. boundary conditions, the fracture model, and the specimens used [ 17 20 ]. All of these have a pronounced impact on the biomechanical outcome parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Constrained axial compression also results in considerable shear forces and moments and is therefore believed to simulate all relevant forces occurring within the construct [ 39 , 40 ]. Moreover, while some studies applied fatigue testing [ 39 , 11 ], our goal was the assessment of primary stability, following previous studies [ 34 , 17 , 13 ]. Finally, the influence of distal screw length was only assessed for the most common distal radius fracture (AO-23 A3) using a biomechanical fracture model.…”
Section: Discussionmentioning
confidence: 99%
“…Same results were found by Penzkofer et al9) We chose to use three distal screws in this model. Hart et al10) did a biomechanical study that compared dual plating of the distal humerus with either one or three screws in the distal ulna column for AO/OTA A3 type fractures. This study showed that the constructs with three distal screws had a higher stiffness in axial loading and bending.…”
Section: Discussionmentioning
confidence: 99%
“…VLDRP dohave a distinct advantage over any other treatment method as they allow immediate postoperative mobilisation[ 11 ], provided optimal placement of the plate/screw construct is achievedintraoperatively. Biomechanical studies[ 12 - 15 ] and clinical observations[ 16 - 20 ] indicate the best placement of the distal locking screws is as close as possible to the subchondral area of the joint to prevent loss of postoperative reduction. The aim of our study was to evaluate the relationship between distal screw placement and postoperative radial shortening in a large consecutive cohort of dorsally displaced distal radius fractures plated with VLDRP.…”
Section: Introductionmentioning
confidence: 99%